Porphyrin-Based Compounds: Synthesis and Application - Carlos J. P. Monteiro; M. Amparo F. Faustino; Carlos Serpa (Molecules, 2023)
Porphyrin-based compounds are an attractive and versatile class of molecules that have attracted significant attention across different scientific disciplines [...]